2019
DOI: 10.1111/vsu.13209
|View full text |Cite
|
Sign up to set email alerts
|

Standing myotomy to treat fibrotic myopathy: 22 cases (2004–2016)

Abstract: Objective: To report the clinical and diagnostic findings associated with fibrotic myopathy, describe the surgical procedure for standing fibrotic myotomy and report postoperative outcomes. Study design: Retrospective study. Sample population: Twenty-two horses. Methods: Records were included if a clinical diagnosis of fibrotic myopathy was based on clinical and/or ultrasonographic examination and the horse was treated with myotomy of the affected muscle. Records were reviewed for signalment, preoperative find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…3,[6][7][8] Alternative treatments include standing laser fibrotomy, myotomy of the affected muscle, and semitendinosus myotenectomy. 1,8,9 Intraoperative ultrasonographic guidance offers multiple advantages to the surgeon, including identification of relevant anatomical structures and avoidance of iatrogenic damage to these structures. 10 Although other minimally invasive ultrasound-guided techniques for tenotomies have been described in the veterinary literature, including tenotomy of the deep digital flexor tendon or annular ligament desmotomy, 11,12 minimally invasive semitendinosus tenotomy has not been described previously in horses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[6][7][8] Alternative treatments include standing laser fibrotomy, myotomy of the affected muscle, and semitendinosus myotenectomy. 1,8,9 Intraoperative ultrasonographic guidance offers multiple advantages to the surgeon, including identification of relevant anatomical structures and avoidance of iatrogenic damage to these structures. 10 Although other minimally invasive ultrasound-guided techniques for tenotomies have been described in the veterinary literature, including tenotomy of the deep digital flexor tendon or annular ligament desmotomy, 11,12 minimally invasive semitendinosus tenotomy has not been described previously in horses.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers in several studies have demonstrated contradictory results in terms of outcomes using the technique in horses with only the semitendinosus muscle affected compared with horses in which the gracilis and/or semimembranosus muscles were also involved 3,6‐8 . Alternative treatments include standing laser fibrotomy, myotomy of the affected muscle, and semitendinosus myotenectomy 1,8,9 …”
Section: Introductionmentioning
confidence: 99%